Formação de futuros professores na organização do ensino de matemática para os anos iniciais do ensino fundamental: aprendendo a ser professor em um contexto específico envolvendo medidas - Pozebon, Simone (2014)
Departing from the theoretical assumptions of the Historical-Cultural Theory, of the Activity Theory, of the Teaching Guiding Activity, as well as authors that approach the training of teachers who teach mathematics, this research has as its main concern the appropriation of theoretical knowledge and the teaching learning for future teachers of the early years. Our main goal is to investigate the training of future teachers in a specific context of organization of the measurement teaching for the early years of Elementary School, which involve study, planning, implementation and evaluation of the pedagogical activities. This research was conducted by a research group, Group of Research and Studies in Mathematical Education GEPEMat, in the project ―Mathematical Education in the early years of Elementary School: principles and practices of the teaching organization‖, sponsored by OBEDUC/CAPES. More specifically it is focused on an extension project the CluMat linked to the one previously mentioned, which develops actions with the early years involving mathematical contents in public schools of Santa Maria/SM since the year 2009.Thus, this research is focused on the actions that the students of Education and Mathematics Degree, members of the group, developed in CluMat in a third grade class of elementary school in a state school. As procedures for data collection we used a researcher s diary, as well as, audio and video recordings from fifteen meetings and photographic records. The data were organized based on four guiding principles that defined the panorama of the analysis: the initial discussions for the study; the planning movements and organization of activities; the mathematical knowledge in the development of the didactic unit; and the teaching learning from the evaluation of the students. Based on the systematization of information through these axes, we used the concept of episodes proposed by Moura (2000) to analyze them. From the analysis, we found indications that there was an attribution of new meanings to the actions that compose the pedagogical activity, and that these new insights, together with the needs that mobilized the students, and the appropriation of necessary mathematical knowledge to the teacher practice, were a movement of teaching learning.